Influence of partial replacement of calcined red clay by gypsum-bonded casting investment waste on geopolymerization reaction of red clay-based geopolymer - Sitthisak Prasanphan; Sujitra Onutai; Nithiwach Nawaukkaratharnant (Heliyon, 2024)
The main objective of this research is to study the influence of partial replacement of calcined red clay by gypsum-bonded casting investment waste (GCIW) from precious metal casting process on geopolymerization reaction of a red clay-based geopolymer. Calcined red clay was partially replaced by GCIW powder with different contents before mixing with sodium-based alkali activator solution to produce the geopolymers. The results indicate that the GCIW significantly impacted the reaction of flesh geopolymers detected by Differential scanning calorimetry (DSC). The reaction products (hydration products and others) of 28-day geopolymers detected by Fourier transform Infrared spectroscopy (FTIR) and X-ray diffractometry (XRD) were employed to support the reaction results. Moreover, the relation between reaction products and compressive strength was discussed. This work concluded that the calcium sulfate compounds contained in GCIW play an important role on geopolymerization reaction, reaction products, and mechanical properties of geopolymer. Furthermore, the results could be employed to propose a reaction mechanism that occurred in geopolymers. The potential use of GCIW as an additive for red clay-based geopolymer bricks preparation was confirmed in this research.